Efeito da quercetina na sinalização purinérgica e no metabolismo oxidativo-inflamatório em modelo de artrite - Saccol, Renata da Silva Pereira (2018)
Rheumatoid arthritis (RA) is a chronic, autoimmune, inflammatory disease with predominant involvement of the small joints, progressive destruction of cartilage and bone, and extra- articular manifestations such as liver, kidney, and vascular damage. The purinergic signaling system plays an important role in the modulation of inflammatory and immune responses through extracellular biomolecules, such as adenine nucleotides, and its adenosine derivative, whose extracellular concentrations are controlled by ectoenzymes (E-NTPDase, E- 5´nucleotidase, and E-ADA) present on the surface of several cells. Besides, numerous studies have demonstrated the involvement of oxidative stress in the pathogenesis of inflammatory arthropathies, such as RA. Quercetin is a flavonoid present in several foods and with well- established anti-inflammatory and antioxidant properties in different experimental models of chronic diseases. In the present study, the effect of quercetin on purinergic signaling and oxidative inflammatory metabolism in model of adjuvant-induced arthritis (AIA) was investigated. Female Wistar rats were divided into groups with and without induction of arthritis. Arthritis score, paw edema, and thermal hyperalgesia were performed before induction. In the arthritis groups, the complete Freund's adjuvant (CFA) was then injected into the hind paw and, after 15 days induction, for confirmation, these tests were repeated. On the 15th day, saline and quercetin treatments started at doses of 5, 25 and 50 mg / kg for 45 days. At the end of the treatment, the tests for evidence of arthritis were repeated, in addition to the activity of ectoenzymes in lymphocytes. Oxidative stress parameters were analyzed in serum, plasma, and hepatic and renal tissue, as well as serum hepatic enzymes, plasma myeloperoxidase activity, IFN-γ and IL-4 levels in serum, and DNA damage markers. The results demonstrated that an inflammatory process was generated, as seen by the increase in the arthritis score and paw edema and the reduction of the thermal hyperalgesia. There was also an increase in E-NTPDase activity and a decrease in E-ADA activity in lymphocytes, in addition to an increase in AST levels, myeloperoxidase activity, IFN-γ and IL-4 secretion, as well as levels of EROs in serum, liver, and kidney EROs, plasma T-BARS, increased DNA damage, and decreased antioxidant enzymes catalase (CAT) and superoxide dismutase (SOD). The treatment with quercetin reduced the signs and symptoms of arthritis, besides altering the activities of the ectoenzymes, reducing the levels of AST and DNA damage, and protect against damage caused by oxidative stress.  Thus, we can suggest that quercetin showed an excellent anti-inflammatory and antioxidant effect, proving to be a promising candidate for adjuvant therapy for the treatment of rheumatoid arthritis.